Overcriminalization dalam Perundang-Undangan di Indonesia - Mahrus Ali (Fakultas Hukum Universitas Islam Indonesia, 2018)
Criminalization in legislation tends to increase, and most of it deals with administrative violations with the potential to cause over-criminalization. This study aims to analyze the concept of over-criminalization and its various forms in criminal legislation. As normative legal research, this study uses a conceptual and statutory approach. The results show that over-criminalization is generally conceptualized in relation to criminalization. The forms also include re-criminalization of an act having been banned by other laws, formulation of offenses without sufficient error requirements, criminalization of impeccable deeds, formulation of offenses without fulfilling the principle of lex certa, criminalization of pure administrative violations, and criminal penalties incomparable to the seriousness of the offenses. The forms of over-criminalization in legislation are obvious in different articles in Law on Plantations, Law Environmental Protection, and Management, and Law on Mineral and Coal Mining.